Inguinal Hernia - Canonico, Silvestro (IntechOpen, 2014)
The surgical treatment of hernia requires an extensive knowledge and technical ability. Astley Cooper stated that no disease of surgical interest requires so broad skills and knowledge as hernia and its variants. The history of groin hernia repair evolved from life-saving procedures (such as for incarcerated hernias) to elective operations performed as day-surgery procedure. The present book is designed to focus on specific topics and problems which a general surgeon dealing with groin hernia is very likely to face during his practice. Its aim is to provide the readers with informative and practical indications to understand, diagnose, and manage patients presenting these situations. It could hopefully stimulate further innovative studies and techniques suitable for treatment of these patients.